Verify the identity

Here is another way to verify by working on both side together,

cot^2x - cos^2x = cot^2x * cos^2x, where cot^2x = (cos^2x)/(sin^2x)

Substitute cot^2x and multiply the second term with (sin^2x)/(sin^2x) for common denominator

(cos^2x)/(sin^2x) -( cos^2x)(sin^2x)/(sin^2x) = (cos^2x)/(sin^2x) * cos^2x

Multiply by sin^2x on both sides to eliminate denominator and factor, then

cos^2x(1 - sin^2x) = cos^2x * cos^2x

Devide by cos^2x on both sides

1- sin^2x = cos^2x, where 1 - sin^2x = cos^2x

Then, cos^2x = cos^2x, both sides same.

## Comments